2014
DOI: 10.3177/jnsv.60.429
|View full text |Cite
|
Sign up to set email alerts
|

Pycnogenol Supplementation Promotes Lipolysis via Activation of cAMP-Dependent PKA in <i>ob/ob</i> Mice and Primary-Cultured Adipocytes

Abstract: Summary This study investigated the PKA-dependent inhibitory effect of pycnogenol (Pyc) on lipolysis using ob/ob mice and primary mouse adipocytes. Supplementation of Pyc at 30 mg/kg significantly reduced body weight gain and visceral fat mass. The serum and hepatic triglyceride (TG) and total cholesterol (TC) levels were reduced by Pyc supplementation, and high density lipoprotein (HDL)-cholesterol level significantly increased. In addition, hormone sensitive lipase (HSL) and adipose triglyceride lipase (ATGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…In this study, we evaluated the effects of PYC on hepatic steatosis and further explored the underlying mechanism in ApoE-deficient mice. Previous studies have shown that PYC effects the regulation of lipid metabolism and possesses protective effects on nonalcoholic steatohepatitis (5,18,38). In line with previous results, we found that PYC reduced body weight gain and decreased plasma lipid and hepatic lipid accumulation in ApoE-deficient mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we evaluated the effects of PYC on hepatic steatosis and further explored the underlying mechanism in ApoE-deficient mice. Previous studies have shown that PYC effects the regulation of lipid metabolism and possesses protective effects on nonalcoholic steatohepatitis (5,18,38). In line with previous results, we found that PYC reduced body weight gain and decreased plasma lipid and hepatic lipid accumulation in ApoE-deficient mice.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, intracellular lipolysis stimulates the breakdown of TGs stored in LDs for subsequent metabolism, and HSL is the rate-limiting enzyme in fat catabolic pathways in adipocytes as well as nonadipocytes. Previous studies have shown that PYC promotes lipolysis in adipocytes (18). We found that the expression of the HSL gene was increased in the liver after supplementation with PYC.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It has been proved that increased PKA activity specifically in adipose tissue could upregulate UCP1 expression and ameliorate metabolism discords. PKA activates p38 MAPK and increases the expression of UCP1, thereby promoting thermogenesis in BAT [75,76]. Moreover, increased PKA activity has also been linked to induction of browning in sWAT [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…It might act through increasing the concentration of hormone sensitive lipase and adipose triglyceride lipase in adipose tissue. Also, it can promote lipolysis by decreasing the activity of prilipin A and fatty acid synthetase (Ho, Kim, Nam, Jun, & Lee, ). Pycnogenol reduces LDL‐C concentration via inhibiting cholesterol biosynthesis, upregulating hepatic LDL‐C receptor and increasing sterol excretion (Kurowska et al, ).…”
Section: Discussionmentioning
confidence: 99%